Statistical analysis of MMS observations of energetic electron escape observed at/beyond the dayside magnetopause. Issue 9 (20th September 2017) - Cohen, Ian J.; Mauk, Barry H.; Anderson, Brian J.; Westlake, Joseph H.; Sibeck, David G.; Turner, Drew L.; Fennell, Joseph F.; Blake, J. Bern; Jaynes, Allison N.; Leonard, Trevor W.; Baker, Daniel N.; Spence, Harlan E.; et al.
Abstract: Observations from the Energetic Particle Detector (EPD) instrument suite aboard the Magnetospheric Multiscale (MMS) spacecraft show that energetic (greater than tens of keV) magnetospheric particle escape into the magnetosheath occurs commonly across the dayside. This includes the surprisingly frequent observation of magnetospheric electrons in the duskside magnetosheath, an unexpected result given assumptions regarding magnetic drift shadowing. The 238 events identified in the 40 keV electron energy channel during the first MMS dayside season that exhibit strongly anisotropic pitch angle distributions indicating monohemispheric field‐aligned streaming away from the magnetopause. A review of the extremely rich literature of energetic electron observations beyond the magnetopause is provided to place these new observations into historical context. Despite the extensive history of such research, these new observations provide a more comprehensive data set that includes unprecedented magnetic local time (MLT) coverage of the dayside equatorial magnetopause/magnetosheath. These data clearly highlight the common escape of energetic electrons along magnetic field lines concluded to have been reconnected across the magnetopause. While these streaming escape events agree with prior studies which show strong correlation with geomagnetic activity (suggesting a magnetotail source) and occur most frequently during periods of southward IMF, the high number of duskside events is unexpected and previously unobserved. Although the lowest electron energy channel was the focus of this study, the events reported here exhibit pitch angle anisotropies indicative of streaming up to 200 keV, which could represent the magnetopause loss of >1 MeV electrons from the outer radiation belt. Plain Language Summary: Although extremely powerful, the Sun does not produce many energetic charged particles. However, lower energy particles originating from the Sun (and Earth) can be energized through multiple processes by the Earth's magnetic field. As such, energetic particles are primarily found within the region of space dominated by the Earth's magnetic field, known as the "magnetosphere." Despite this fact, energetic particles are still commonly found outside of the magnetosphere. This raises questions as to where these particles come from and how they get there. The study presented here shows new observations of energetic particles (specifically focusing on electrons) from the Magnetospheric Multiscale (MMS) spacecraft. These observations show that the energetic electrons seen outside the magnetosphere are in fact coming from inside the magnetosphere and are escaping via a mechanism known as magnetic reconnection, where magnetic field lines from the Earth and Sun meet and are reconfigured. The reorientation of these field lines during reconnection provides an easy avenue of escape for energetic electrons within the magnetosphere. Although this loss process is minimal in terms of the total number of particles in the magnetosphere, it is fundamental for our understanding of the intrinsic processes of near‐Earth space. Key Points: The 238 field‐aligned 40 keV electron streaming events are identified in MMS magnetosheath observations Statistically, electron escape/streaming from the magnetosphere occurs across all MLT on the dayside Results support the conclusion that these energetic electrons escape via reconnected field lines